STRUCTURAL DIVERSITY OF LOG OF Eucalyptus spp. GENOTYPES - LOPES, OLÍVIA PEREIRA; Castro, Jonnys Paz; de Arruda, Tatiana Paula Marques; Latorraca, João Vicente de Figueiredo; Mori, Fábio Akira (Floresta, 2019)
Anatomical studies, besides being useful in the identification of the species, make it possible to generate information about the structure of the log in order to identify the relationships between the log and the technological properties of the wood. The aim of this work was to anatomically characterize the log of different genotypes of the genus Eucalyptus planted in the state of Minas Gerais – Brazil and to describe its main differences and/or similarities. Three genetically improved genotypes were evaluated, Eucalyptus urophylla x Eucalyptus grandis; Eucalyptus urophylla and Eucalyptus urophylla x Eucalyptus camaldulensis , aged whithin 6 to 7 years old. Discs of 9 trees were removed at breast height (1.30 meters from the ground). From each disk, specimens were obtained in the medulla-cambial direction with dimensions of approximately 2 cm³ to make permanent sheets, being that the anatomical characterization of the genotypes followed the recommendations of the IAWA Committee (1989). The results showed that the genotypes of Eucalyptus are very similar, however, differences were observed in the axial parenchyma and in the composition of rays.